Banker to the poor micro-lending and the battle against world poverty - Yunus, Muhammad (Blackstone, 1999)
In 1983, Muhammad Yunus established Grameen, a bank devoted to providing the poorest of Bangladesh with miniscule loans. Based on the belief that credit is a basic human right, not the privilege of a few, Grameen Bank now provides over 2.5 billion dollars of micro-loans to more than two million families in rural Bangladesh. Ninety-four percent of Yunus's clients are women, and repayment rates are nearly 100 percent. It was an idea born on a day in 1976 when he loaned
Read by Ray Porter
Keywords: Yunus, Muhammad, 1940-